Dynamic web/cloud services - Foo, Yong Zheng. (2011)
Elderly users are often the last portions of the consumer market to embrace technology changes. From a market segment that was previously ignored by the IT industry, the shift in the world demographics has now place the elderly consumers back into the limelight. With most consumers gaining more mobility, mobile devices have seen several improvements to cater the increasing appetite of mobile users. Mobile device companies have also began to churn out devices that are elderly friendly, highlighting the impending change in consumer demographics. It will be a challenge to create new services from upcoming or current technologies that will interest the elderly. SOAP Web Services have defined the way businesses communicate with other businesses' services. The XML-compatible architecture made multi-system interoperability possible and yet preserved the middleware concept. The advancement made by Cloud Computing introduced numerous opportunities for businesses by removing the physical constraints of actual hardware. Major providers of this paradigm include Amazon with Amazon Web Services (AWS) and Google with Google Apps, which have tremendous market share in this sector. By combining the popularity of mobile devices and the advancement of both Web and Cloud technology, new services can be created to target growing elderly consumer market. The proposed conceptual Cloud-based Service Repository model would resemble the typical Web Service Architecture and provide an integrated configuration with Google App Engine, SOAP Web Services and the iPhone. The integrated architecture allows connectivity over the Cloud network with an iPhone.